Integration of Islamic Input in Medical Curriculum Universiti Sains Islam Malaysia (USIM) Experience - Jamilah, J; Najib, AA; Dzulkhairi, MR; Ariff, HO; Ismail, NMN (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS/Scopus